Neuropilin 2 in osteoblasts regulates trabecular bone mass in male mice - Verlinden, Lieve; Doms, Stefanie; Janssens, Iris; Meyer, Mark B.; Pike, J. Wesley; Carmeliet, Geert; Verstuyf, Annemieke (Frontiers in Endocrinology, 2023)
Introduction Neuropilin 2 (NRP2) mediates the effects of class 3 semaphorins and vascular endothelial growth factor and is implicated in axonal guidance and angiogenesis. Moreover, NRP2 expression is suggested to be involved in the regulation of bone homeostasis. Indeed, osteoblasts and osteoclasts express NRP2 and male and female global Nrp2 knockout mice have a reduced bone mass accompanied by reduced osteoblast and increased osteoclast counts. Methods We first examined the in vitro effect of the calciotropic hormone 1,25-dihydroxyvitamin D3 [1,25(OH)2D3] on Nrp2 transcription in osteoblasts. We next generated mice with a conditional deletion of Nrp2 in the osteoblast cell lineage under control of the paired related homeobox 1 promoter and mice with a conditional Nrp2 knockdown in osteoclasts under control of the Lysozyme promoter. Mice were examined under basal conditions or after treatment with either the bone anabolic vitamin D3 analog WY 1048 or with 1,25(OH)2D3. Results and discussion We show that Nrp2 expression is induced by 1,25(OH)2D3 in osteoblasts and is associated with enrichment of the vitamin D receptor in an intronic region of the Nrp2 gene. In male mice, conditional deletion of Nrp2 in osteoblast precursors and mature osteoblasts recapitulated the bone phenotype of global Nrp2 knockout mice, with a reduced cortical cross-sectional tissue area and lower trabecular bone content. However, female mice with reduced osteoblastic Nrp2 expression display a reduced cross-sectional tissue area but have a normal trabecular bone mass. Treatment with the vitamin D3 analog WY 1048 (0.4 μg/kg/d, 14 days, ip) resulted in a similar increase in bone mass in both genotypes and genders. Deleting Nrp2 from the osteoclast lineage did not result in a bone phenotype, even though in vitro osteoclastogenesis of hematopoietic cells derived from mutant mice was significantly increased. Moreover, treatment with a high dose of 1,25(OH)2D3 (0.5 μg/kg/d, 6 days, ip), to induce osteoclast-mediated bone resorption, resulted in a similar reduction in trabecular and cortical bone mass. In conclusion, osteoblastic Nrp2 expression is suggested to regulate bone homeostasis in a sex-specific manner.